The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10899-010-9188-y
|View full text |Cite
|
Sign up to set email alerts
|

Internet Gamblers: A Latent Class Analysis of Their Behaviours and Health Experiences

Abstract: In order to learn about the behaviours and health experiences of people who gamble on the Internet, we conducted an international online survey with respondents recruited via gambling and gambling-related websites. The mean (SD) age of the 4,125 respondents completing the survey was 35.5 (11.8) years, with 79.1% being male and 68.8% UK residents. Respondents provided demographic details and completed validated psychometric screening instruments for problem gambling, mood disturbances, as well as alcohol and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 35 publications
4
46
0
1
Order By: Relevance
“…Consistent with previous research, overall involvement did appear to be related to problem gambling (Gainsbury et al, in press a;Holtgraves, 2009;LaPlante et al, 2009;Philander & MacKay, in press), as shown by MMGs having the highest participation rates in multiple activities and the highest average PGSI scores. This is consistent with the analysis of UK gamblers, which found that online-only gamblers who only played a few forms of gambling were less likely to experience gambling problems (Lloyd et al, 2010). These results suggest that participating in multiple gambling activities may be a risk factor for gambling problems which is supported by IGs engaging in the lowest number of different activities and having the lowest problem gambling rates.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with previous research, overall involvement did appear to be related to problem gambling (Gainsbury et al, in press a;Holtgraves, 2009;LaPlante et al, 2009;Philander & MacKay, in press), as shown by MMGs having the highest participation rates in multiple activities and the highest average PGSI scores. This is consistent with the analysis of UK gamblers, which found that online-only gamblers who only played a few forms of gambling were less likely to experience gambling problems (Lloyd et al, 2010). These results suggest that participating in multiple gambling activities may be a risk factor for gambling problems which is supported by IGs engaging in the lowest number of different activities and having the lowest problem gambling rates.…”
Section: Discussionsupporting
confidence: 88%
“…The majority of UK Internet gamblers use the Internet for single gambling activities and have few gambling problems (Lloyd et al, 2010). In contrast, multi-activity gamblers were more likely to be male, single, unemployed with below-average income, and most likely to experience gambling problems.…”
Section: Introduction and Literature Reviewmentioning
confidence: 98%
“…Similarly, many of these studies only consider one single type of poker player-often online-making it difficult to identify the existence of subgroups among poker players. However, latent class studies conducted among Internet gamblers show that these Internet gamblers are heterogeneous and composed of several subgroups, differing markedly on both demographic and clinical characteristics (Lloyd et al 2010 ).…”
Section: Studies Of Poker Playersmentioning
confidence: 99%
“…The primary advantage of LCA over alternative approaches, such as cluster analysis, is the reliance on a model-based method for estimating population characteristics derived from sample data, adjustment of estimates for measurement error, formal statistical procedures for determining the number of classes, use of probabilities as the basis for interpretation of results, and flexible treatment of variance among classes (Magidson and Vermunt 2002;Nylund et al 2007 ). Although, not yet used in poker research, LCA has been reported in recent studies interested in the existence of a specific pattern of gambling activities in different populations (Boldero et al 2010 ;Cunningham-Williams and Hong 2007 ;Goodriaan et al 2009 ;Lloyd et al 2010 ).…”
Section: Studies Of Poker Playersmentioning
confidence: 99%
“…Les JHA ne peuvent donc pas, du point de vue des participants, et de certains chercheurs, être conceptualisés comme étant des activités homogènes présentant les mêmes facteurs de risque (Dickerson, 1993 ;Bjerg, 2010 ;Lloyd et al, 2010). En fait, des chercheurs vont même jusqu'à suggérer que des processus psychologiques différents et spécifi ques seraient mis en oeuvre lors du développement du jeu pathologique selon le type de jeu (Dickerson, 1993 ;Petry, 2005).…”
Section: Discussion Et Conclusionunclassified